Arduino based Hardware Implementation of Automatic Side Stand for Motor Bike - Joy Mathavan, J.; Premathilaka, P.G.S.G.; Dinakara, K.G.L.; Herath, H.M.T.D. (International Conference on Computing Methodologies and Communication (ICCMC 2020) IEEE Xplore, 2020)
Usage of motor bike is preferred by most of the people for it is an easy way for transport and it needs a little space comparatively on parking. But when accidents happen, it causes severe injuries and sometimes deaths as well. There are many reasons for these accidents, internally and externally. Forgetting to lift up the side stand is one of the reasons and it could be avoided by certain technical aspects. This paper presents an automatic side stand for motor bikes, which could be lifted up while the bike starts moving and retrieve back when it stops. The design consists of sensors, relay switches and regulators which are controlled by Arduino UNO program. There is no need to additional energy source or any other complexity since the designed system uses the necessary power from the motor bike battery.
Keywords: Automatic motor bike side stand; Smart motor bike; Arduino pro mini; Gear shift system; Lever mechanism; Accidents